Branchial cleft cyst: An unusual site for the cervical metastasis of nasopharyngeal carcinoma. Issue 2 (April 2018) - Liao, Yu-Chang; Adel, Mohamad; Lee, Li-Yu; Chang, Kai-Ping
Abstract: Objective: Cancers found in the resected branchial cleft cyst are rare clinically but usually impose substantive diagnostic and treatment challenges for clinicians. Methods: A 31-year-old man presented with a lateral neck mass that was suspected to be an inflammatory branchial cleft cyst. After excision, the pathologic specimen revealed a benign cystic appearance with a focus of undifferentiated carcinoma. Serologic tests for Epstein–Barr virus were negative. A positron emission tomography scan and upper aerodigestive tract endoscopies were negative for any other suspicious lesion. Results: The patient underwent random biopsies of the nasopharynx, tongue base, and hypopharynx and bil tonsillectomy. Pathologic examination of the nasopharyngeal biopsies showed the presence of undifferentiated carcinoma. The cancerous part of the branchial cleft cyst and this nasopharyngeal specimen were positive for the latent membrane protein-1 and EBV-encoded RNAs of Epstein–Barr virus (EBV) and confirmed our diagnosis. Conclusion: This is the first report of a NPC metastasizing to a branchial cleft cyst. Molecular diagnostic techniques facilitate the definite diagnosis that enabled us to refine treatment plans and offered the patient a favorable outcome.